Melatonin Treatment for Sleep Disorders in Parkinson's Disease: A Meta-Analysis and Systematic Review - Ma, Hongxia; Yan, Junqiang; Sun, Wenjie; Jiang, Menghan; Zhang, Yongjiang (Frontiers in Aging Neuroscience, 2022)
Objective The efficacy of melatonin on sleep disorders in Parkinson's disease (PD) is still unclear. The purpose of this study was to investigate the efficacy of melatonin on sleep disorders in PD by summarizing evidence from randomized clinical trials (RCTs). Methods PubMed, Cochrane Library, EMBASE, and Web of Science databases were searched for studies published before 20 August 2021. Results were analyzed using Review Manager 5.2 software. We used Trial Sequential Analysis (TSA) software to avoid false-positive results caused by random errors. Results We included 7 studies in this systematic review and meta-analysis. The results of the meta-analysis showed that compared with placebo, the subjective sleep quality of patients with PD significantly improved after melatonin treatment (MD = −2.19, 95% CI: −3.53 to −0.86, P = 0.001). In the systematic review, we qualitatively analyzed the efficacy of melatonin on the objective sleep quality of patients with PD, and the results showed that melatonin exerted a positive effect with good safety and tolerability. However, there was no significant improvement in excessive daytime sleepiness assessed by the Epworth Sleepiness Scale (ESS). Conclusion We found that melatonin can significantly improve the subjective and objective sleep quality of patients with PD with good safety and tolerability. Melatonin could be considered an effective treatment for insomnia in patients with PD.